Reservoir characteristics and main controlling factors of argillaceous limestone in the Mao-1 Member, middle permian Maokou formation, southeastern Sichuan basin, southwest China - Yang, Rong; Yang, Xiyan; Zhang, Yu; Du, Yao; Qiao, Lin; Lei, Yunjing; Fan, Xiangyu (Frontiers in Earth Science, 2025)
In recent years, various acidizing tests have been conducted to obtain information about the industrial gas flows from acidizing tests in vertical wells JS1 and YH1 in eastern Sichuan Province, China. The results indicated that the Mao-1 Member of the Maokou Formation in southeastern Sichuan consists of good source rocks and a reservoir with high gas content. In this study, through investigations of outcrop sections, core drilling observations, thin-section identification, SEM, XRD, and TOC measurements, combined with nitrogen adsorption and logging analysis, we systematically studied the characteristics of tight argillaceous limestone reservoirs in the Mao-1 Member of southeastern Sichuan and summarized the main controlling factors for their formation. In the study area, the reservoir lithologies of the Mao-1 Member were composed of micrite limestone, bioclastic micrite limestone, and argillaceous limestone. Argillaceous limestone exhibited the highest content of clay minerals and TOC, while bioclastic micrite limestone showed relatively lower values. Six types of reservoir spaces were identified: intergranular pores, solution pores, organic pores, bioclastic-related fractures, clay mineral interlayer fractures, and macroscopic fractures. Argillaceous limestone also exhibited relatively high porosity in the Mao-1a subsegment. The reservoir pores are mainly divided into micro-pores and medium-pores, with diameters of less than 4 nm. The reservoir is primarily distributed vertically in the Mao-1a sub-member and the upper part of the Mao-1c sub-member. The formation of the tight carbonate reservoir is primarily influenced by diagenetic processes, including rock type, mineral composition, pore type, organic matter content, clay mineral transformation, dissolution, and cementation. Our analysis demonstrated that argillaceous limestone with high TOC content and good porosity is the best reservoir rock type in the study area.